2007
DOI: 10.1007/s10620-006-9147-8
|View full text |Cite
|
Sign up to set email alerts
|

The Serum Endothelın-1 Level in Steatosıs and NASH, and Its Relatıon wıth Severıty of Lıver Fıbrosıs

Abstract: Endothelin-1 (ET-1) is known to play an important role in hepatic fibrosis. ET-1 is also a mediator that is elevated in conditions such as insulin resistance, hyperglycemia, oxidative stress, and endothelial cell dysfunction. In this study, we investigated whether ET-1 has a role in determining the severity of liver fibrosis in NASH. Also, the relation between ALT levels, obesity, diabetes, and AST/ALT ratio and fibrosis and ET-1 level was sought. A total of 92 patients were enrolled in the study. The patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 33 publications
1
24
0
1
Order By: Relevance
“…), which limit their use [10][11][12][13]. Fibroscan has been recently introduced as a noninvasive method for diagnosing liver fibrosis in patients with nonalcoholic fatty liver, but more studies are needed to validate its usefulness [14].…”
Section: Discussionmentioning
confidence: 99%
“…), which limit their use [10][11][12][13]. Fibroscan has been recently introduced as a noninvasive method for diagnosing liver fibrosis in patients with nonalcoholic fatty liver, but more studies are needed to validate its usefulness [14].…”
Section: Discussionmentioning
confidence: 99%
“…4), since Bala et al (2010) have found two predicted target sites in SMAD2 3′UTR. In non-alcoholic steatohepatitis (NASH) patients, where fat accumulation leads to inflammation and subsequent fibrosis, Degertekin et al (2007) observed that the serum ET-1 level showed a statistically significant increase as fibrosis severity increased. This ET-1 increase could well be mediated by the difference in expression of hepatic miRNAs such as miRNA 155, as was observed in a mouse model of dietary, non-alcoholic steatohepatitis (Pogribny et al, 2010).…”
Section: Mirna 155mentioning
confidence: 99%
“…4). It could be identified in the liver (Yeligar et al, 2009;Degertekin et al, 2007), lung (Crestani, 2007;Jain et al, 2007) and kidney (Oba et al, 2010) as well as in tumors, such as ovarian cancer (Bagnato and Rosano, 2007;Rosano et al, 2011;Vergara et al, 2009). Epithelial-mesenchymal transition (EMT) is a prime example of a reversible differentiation process that occurs during normal development, such as neural tube and mesoderm formation during embryogenesis [Type I EMT, (Carew et al, 2011)].…”
Section: Mirna 195mentioning
confidence: 99%
See 1 more Smart Citation
“…Asimismo, se han relacionado con la fibrosis, la HTA, la hiperferritinemia, una marcada hipertrigliceridemia, la historia familiar de EHNA o de cirrosis criptogenética, la obesidad central, un IMC superior a 31 y un cociente HOMA/adiponectinemia elevado 47,48 . Los niveles séricos de endotelina-1 también se relacionan con el grado de fibrosis 50 . Por otro lado, la fibrosis hepática se puede predecir mediante la estimación de parámetros directamente relacionados con la fibrogéne-sis, solos o en combinación.…”
Section: Marcadores Clínicos Y Serológicos Indicativos De Esteatohepaunclassified